(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
The wireless sensor network (WSN) consists mostly of a large number of nodes in a large area where not all nodes are directly connected. The applications of comprise a wide variety of scenarios.The mobile nodes are free to move because this network has selfــstructured topology. Routing protocols are responsible for detecting and maintaining paths in the network, and it classified into reactive (OnـــDemand), proactive (Table driven), and hybrid. In this paper represents a performance study of some WSN routing protocols: the Dynamic Source Routing (DSR), Ad hoc On-Demand Distance Vector (AODV), and Destination-Sequenced Distance-Vector (DSDV). The comparison made according to important metrics like packet delivery ratio (PDR), total packets dropped, Average end-to-end delay (Avg EED), and normalized routing load under the Transmission Control Protocol (TCP) and User Datagram Protocol (UDP) traffic connection and with varying number of nodes, pause time; and varying speed. In this work used (NSــ2.35) that installed on (Ubuntu 14.04) operating system to implementing the scenario. Conclude that the DSR has better performance in TCP connection; while the DSDV has better performance in UDP protocol.